체육학 연구를 위한 다층자료 회귀분석(위계선형모형)의 소개 - 박일혁(Il Hyeok Park); 이기봉(Gee Bong Lee); 서성혁(Sung Hyeok Suh) (한국체육측정평가학회지, 2010)
본 tutorial은 다층자료의 회귀분석(위계선형모형)을 소개하기 위한 것이다. 위계선형모형은 다층자료를 분석함으로써 대상자의 특성변인 뿐 아니라 대상자가 속한 상위 집단의 특성변인으로 종속변인을 설명하는 통계모형이다. 이 통계모형은 개념적으로 일반적으로 실시되는 회귀분석 모형에서 나타나는 절편과 회귀계수를 상위집단의 특성변인, 즉 2층 자료의 변인으로 설명(예측)하는 회귀모형으로 1층과 2층 자료 또는 그 이상의 자료에 대한 여러 번의 회귀 모형으로 이해할 수 있다. 특히 위계선형모형은 반복측정된 자료에 대한 변화의 분석에 적용하여 변화에 대한 설명변인의 효과를 검증할 수 있어 매우 유용하게 이용된다. 본 tutorial에서는 위계선형모형이 일반적으로 적용되는 두 가지 경우에 대한 기본 개념 설명과 자료 분석 및 해석의 예를 제시하였다. This is a tutorial paper introducing hierarchical linear modeling (HLM) for the applied research in the area of exercise and sport science. The HLM was introduced more than 40 years ago, but has not been used often in research. The HLM can be viewed as two or more regression modelings for the analysis of multilevel data. This statistical technique is especially useful in educational and organizational research where the data is typically multilevel. Application of the HLM in analyzing repeated measures data for the analysis of change is also very useful. In the paper, the basic concepts of HLM is introduced using less technical terms, and the analyses examples are presented with simulated data and real data. The strengths and weaknesses of this statistical technique is also discussed. KCI Citation Count: 6